Enhancing Rubberwood Properties via Sodium Silicate Modification: A Study on Mechanical and Thermal Stability - Zi You; He Sun; Yayun Wu; Zhiwei He; Yuxing Han; Shiqi Zeng; Taian Chen (BioResources, 2025)
Rubberwood (RW), a commercially valuable timber species widely used for mid-to-high-end wood products in Yunnan, was modified through full-cell impregnation with sodium silicate (SS) solutions at varying concentrations (10 to 30%). The treatment significantly improved the wood's performance, overcoming challenges such as achieving optimal impregnation while preserving its integrity. Comprehensive analysis indicated that a 20% sodium silicate solution provided the most effective modification. This optimal treatment increased compressive strength by 15% (78.8 MPa), increased modulus of elasticity by 35.7% (1900 MPa), and reduced water absorption by 13.3% (103.5%) compared to untreated samples. Microstructural analysis confirmed optimal impregnation at 20%, with Fourier Transform Infrared (FTIR) spectroscopy revealing Si-O-Si peaks and X-ray photoelectron spectroscopy (XPS) indicating the presence of silicon, confirming the successful penetration of sodium silicate and silica formation. Furthermore, X-ray diffraction (XRD) analysis indicated that there was no alteration in the position of the cellulose diffraction peaks, which demonstrated that the sodium silicate impregnation treatment did not destroy its crystalline structure. This modification enhanced the mechanical properties and thermal stability of rubberwood while providing an eco-friendly alternative to traditional chemical treatments. Sodium silicate, mildly toxic and abundant, offers a sustainable solution for improving wood quality in various applications.